2018
DOI: 10.1038/s41598-018-21744-9
|View full text |Cite
|
Sign up to set email alerts
|

Sub-cellular In-situ Characterization of Ferritin(iron) in a Rodent Model of Spinal Cord Injury

Abstract: Iron (Fe) is an essential metal involved in a wide spectrum of physiological functions. Sub-cellular characterization of the size, composition, and distribution of ferritin(iron) can provide valuable information on iron storage and transport in health and disease. In this study we employ magnetic force microscopy (MFM), transmission electron microscopy (TEM), and electron energy loss spectroscopy (EELS) to characterize differences in ferritin(iron) distribution and composition across injured and non-injured ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…A combined Perls-hematoxylin-eosin stain was also proposed to easily check the presence of ferric iron in tissue sections [13]. Moreover, an immunohistochemical technique can be used to detect the presence of ferritin in tissue samples with results equivalent to Perls stain [14]. Therefore, Perls stain may be used to identify excess iron deposits caused by oxidative damage mechanism in COVID-19 patients.…”
mentioning
confidence: 99%
“…A combined Perls-hematoxylin-eosin stain was also proposed to easily check the presence of ferric iron in tissue sections [13]. Moreover, an immunohistochemical technique can be used to detect the presence of ferritin in tissue samples with results equivalent to Perls stain [14]. Therefore, Perls stain may be used to identify excess iron deposits caused by oxidative damage mechanism in COVID-19 patients.…”
mentioning
confidence: 99%
“…Applications of MFM have also extended to evaluate biological samples 12 such as ferritin proteins, 13,14 cells labeled with magnetic particles, 15 and magnetic (iron) deposits in bacteria 16,17 and in mammalian tissues. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…For biomedical applications the investigation of hidden nanoparticles such as SPIONs embedded in tissues and the cellular uptake of SPIONs are of increasing interest. The evaluation of iron distribution in biological tissues is important for diagnosis and treatment of a variety of diseases . Blisset et al characterized the difference in ferritin distribution across injured and non‐injured tissues .…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of iron distribution in biological tissues is important for diagnosis and treatment of a variety of diseases . Blisset et al characterized the difference in ferritin distribution across injured and non‐injured tissues . Hautot et al demonstrated that the concentrations of magnetite are found to be significantly higher in Alzheimer's disease brain tissues …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation